Always Measure One Level Deeper. - OUSTERHOUT, JOHN (Communications of the ACM, 2018)
The article discusses the importance of performance measurements in improving the quality of systems being measured and the developers' intuition. Topics include the lack of performance evaluation education and widespread agreement on how to measure performance within the computer science industry, the importance of understanding the system's performance as well as why it performs that way, and the application of the scientific method to improve intuition about systems.